Ostensibly Healthy Forerunners of Non-communicable Diseases (NCD) from Rural KONKAN, India - Patil, Suvarna N. (Current Overview on Disease and Health Vol. 7, 2023)
KONKAN region in the western Indian state of Maharashtra has witnessed undernutrition for many decades. In spite of this non-communicable diseases are on the rise. BKL Walawalkar Hospital launched in 1996 has generated lot of clinical and epidemiological evidence to demonstrate the presence of undernutrition across life course which as per Developmental Origins of Health and Disease hypothesis could be a precursor to onset of adult non-communicable diseases in KOKAN. Poor body mass index or thinness indicating poor nutrition has been observed in this community from fetal to adult life. Our data has also shown poor fetal growth, high prevalence of low birthweight and poor growth in early childhood in the region. Considering that adolescent girls are future mothers, there is an urgent need to focus on adolescent period. Adolescence could be the second window of opportunity Our work of last 2 decades has laid to setting up of a DERVAN cohort study among adolescent girls in the region and it is expected to throw the light on disease biology of non-communicable diseases in KONKAN region of Maharashtra. This review summarizes our work for last 2 decades.